A skeletal disorder in a dog resembling the Klippel–Feil Syndrome with Sprengel's Deformity in humans. (5th September 2014) - Bertolini, G.; Trotta, M.; Caldin, M.
<x xml:space="preserve">Abstract</x> A five‐year‐old intact male golden retriever dog was evaluated for cervical pain and right hemiparesis. Clinical and computed tomography features suggested a caudal cervical instability and myelopathy due to a cervicoscapular malformation resembling the human Klippel–Feil Syndrome with Sprengel Deformity, a rare complex congenital disorder. Polymerase chain reaction (PCR) and direct sequencing of MEOX1, PAX1 and FGFR3 genes were performed in this dog to investigate a possible underlying genetic predisposition, but no mutations were detected in the coding regions of the three target genes evaluated. Other genes can be involved in this condition in dogs and require further investigation. This report describes a cervical vertebral fusion and complex scapular anomaly in a dog. The presence of an omovertebral bone should be considered in the setting of signs characteristic of myelopathy in dogs with or without obvious skeletal deformity.